Using six thinking hats to raise intercultural awareness: A pre-experimental study - Gürsoy, Esim; Özcan, Eda Nur (UNIV GRANADA, 2021)
Due to the increased mobility of the world population driven by technology, people in today's world are interacting more than ever. Globalization reveals the need for intercultural awareness. Therefore, this study aims to raise the intercultural awareness of EFL learners, aged between 12 and 13 through the use of Six Thinking Hats model with several modifications and presents an alternative way for the original model proposed by Edward De Bono. A purposive sampling method was used to select participants assumed to have less intercultural awareness as a result of the pretest. For close and in-depth observation, one group pretest-posttest design was preferred. To track the differences and similarities that occurred in the behaviors of participants during the treatment; qualitative data were collected and analyzed with the use of the constant comparison method. The findings suggested that the modified version of Six Thinking Hats model showed effects on participants' attitudes. Participants' approach to culture-based issues switches from personal judgments to questioning and understanding.
Keywords: intercultural awareness; intercultural communication; parallel thinking; six thinking hats